Modelování jevů z mechaniky ve školské fyzice - Válek, Jan (Odborné a technické vzdělávání, 2023)
Title in English: Modelling Mechanical Phenomena in School Physics The book offers a view of physical modelling in primary school education, especially in mechanics. It has several aims, namely: a description of models in their historical development up to the present day (the emphasis is on applicability to primary school practice); a comparison of selected development environments suitable for the creation of computer models by teachers and pupils; a description of teachers and pupils using and creating models for their own teaching or preparation. Finally, several piloted models that can be applied in school physics are presented. The publication contains three parts: Pedagogical (focusing on the goals in Czech curriculum documents); Theoretical (devoted to digital education and its impact on people and the perception of models by students and teachers); Practical (devoted to the actual creation of models for school practice).